The determinants of regional exchange in Mercosur: geography and trade liberalization - Garriga, Marcelo Jorge (1995)
Since the mid-eighties many Latin American countries have been involved in a process of trade liberalization1. In some cases, the tariff reduction has been quite impressive (see table 1). The obvious consequence of this liberalization was a strong increase in international trade flows between these countries and the rest of the world . This raise in the overall level of international trade has also been accompanied by an even stronger increase in regional exchange of goods and services . For example, in the case of ALADI countries, the rate of change in regional trade between 1987 and 1992 surpasses that corresponding to total trade (see table 2). As a consequence, since 1987, these economies experienced an increase in their share of regional exports and imports on total exports and imports; it rose from 12% in 1987 to 16.5% in 1992. What explains these upsurge in trade flows among Latin America countries? What role have played commercial policies in this phenomenon? . In particular, have unilateral- non preferential--trade liberalization schemes anything to do with this phenomena?. What about the effect of sub-regional liberalizations schemes that became popular in the 1990s ? . How important is geography (distance) and "neighborhood" in explaining this increase in regional trade. The purpose of this paper is to address these questions, concentrating our attention on the countries belonging to MERCOSUR. In particular, we provided some evidence supporting the fact that the important increase in trade flows among Mercosur countries is driven by the exploitation of comparative advantages couple with geographical proximity. Both factors have been encouraged by the unilateral trade liberalization reforms pursued by each nation. The effect of preferential reduction in tariffs has also spurred trade among the four economies. Nevertheless, its contribution is far less important once appropriate control is taken for geography and unilateral liberalization policies